Design of the small-sized nanosecond pulse-periodic electron accelerator - Yuferov, V.B.; Buravilov, I.V.; Zhivankov, K.I.; Pakhomov, A.Y.; Nikulshina, V.V. (Вопросы атомной науки и техники, 2014)
The design features of high-voltage electron nanosecond accelerators based on the Tesla transformer are considered. The construction of the pulse-periodic accelerator with an energy of ~ 300 keV , a current of ~ 10 kA and a pulse duration of ~ 50 ns is given.